Analysis of the effect of formation potential on the electrochemical response of doped titanium oxides. (10th January 2017) - Policastro, Steven A.; Anderson, Rachel M.; Roeper, Donald F.; Horton, Derek J.
Abstract: The electrochemical and semiconductor behavior of oxides of pure Ti and two Ti-based binary alloys, Ti99 Sn1 and Ti99 Cr1, were investigated using electrochemical impedance spectroscopy (EIS), Mott-Schottky analysis, intensity modulated photocurrent spectroscopy (IMPS), and potentiodynamic polarization in order to understand differences in measured oxygen reduction catalytic activity with the goal of suppressing the capability of titanium to drive galvanic corrosion. The combination of EIS techniques with IMPS was used to determine such semiconductor properties as the band gaps, flat band potentials, dielectric constants, defect concentrations, and catalytic properties, i.e., the reaction rate constants, of the oxides. The semiconductor properties of the oxides were observed to change as a function of oxide formation potential but the greatest changes in oxygen reduction rates in an alkaline solution were only found to occur with alloying, with the greatest decrease seen for the Ti99 Sn1 alloy.